Oral field cancerization: Genetic profiling for a prevention strategy for oral potentially malignant disorders - Puspasari, Karlina; Pasaribu, Togu Andrie Simon; Surboyo, Meircurius Dwi Condro; Ayuningtyas, Nurina Febriyanti; Santosh, Arvind Babu Rajendra; Ernawati, Diah Savitri (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: Oral cancer therapy, such as radiation or surgical treatment, has pernicious long-term effects that patients suffer throughout their life, the disability being considerable with delayed diagnosis. It is well known that many oral cancers develop from oral potentially malignant disorders (OPMDs). Patients diagnosed with OPMDs may have an increased risk of developing cancer anywhere in the oral cavity. Early detection and intervention could be essential prevention strategies to inhibit oral cancer progression. OPMDs may not immediately develop into carcinoma. However, this condition provides a